Influence of metal ions on β-D-glucosidase and cell morphology of Rhodotorula glutinis and Rhodotorula mucilaginosa - Alfaro, Juan Manuel (2017)
The cell wall is a complex and dynamic structure. It is also a site of diverse enzyme activities. The balance between its synthesis and lysis is critical, since wall synthesis in the absence of lysis can cause excessive wall thickening and possible growth arrest; while, lysis in the absence of synthesis would produce bursting of the cell. Therefore, within permissible limits, the net balance between wall synthesis and wall lysis will exert a marked influence on the cell growth and morphology. In this work, the b-D-glucosidase activity was firstly selected as a marker of the wall lytic potential of both Rhodotorula glutinis and Rhodotorula mucilaginosa using p-nitrophenyl-β-D-glucopyranoside as substrate. Secondly, a doses-response study involving several metal ions was conducted; as a result, the FeCl3 and MnCl2 significant increased the biomass-bound β-D-glucosidase activity from R. glutinis and R. mucilaginosa, respectively. Thirdly, to test the influence of each metal ion, 6 mM of either FeCl3 (for R. mucilaginosa) or MnCl2 (for R. glutinis) was supplemented to a medium with lower nitrogen content (MLN). The MLN without any addition was taken as the control. Cultures were incubated at 30°C and 180 rpm during six days. Thus, the major and minor diameter of R. mucilaginosa increased from 3.40 ± 0.23 μm to 5.28 ± 0.40 μm and from 2.60 ± 0.23 μm to 5.20 ± 0.55 μm, respectively, in the presence of 6 mM FeCl3. And, the major and minor diameter of R. glutinis increased from 4,90 ± 0.47 μm to 5.48 ± 0.42 μm and from 2.23 ± 0.53 μm to 4.95 ± 0.49 μm, respectively, in the presence of 6 mM MnCl2. So, from these results it might be concluded that the supplementation of either FeCl3 or MnCl2 to the culture medium induced morphological changes in both oleaginous yeasts. In addition, the biomass and lipid concentration obtained after fermentations were also discussed.